Penelitian Peta Posisi Pasar Mobil Sedan Dari Sudut Persepsi Konsumen Di Indonesia - Ridwan, Agus Salim; Muzakkir, Fajri (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
A busting market autonwtizie in Indonesin, encl! ndricle producer efforts to clumge their performanceeven; year. 77re perfomuznce hopped meets consu111es' e.1 . pectntion not only pln;simlly but also psi;clwlogically.Wiren car product from Gneeness and Korean come into Indonesian market, otherIndonesian products effort pretend tl'!eir market before shipped from that new product. So that it isven; interested to find out sedan car consumers' perspective, market position map which can answertire question such as which car tluzt can lose from market?. I11is study is begun from service, personal,price and image values. Consun7er perception is faltered fnJ questioners and is analyzed a dimensionalscale metlwd and preference regression. 77re analysis shows market position map in Indonesia andwill useful not only for bussiness but also for goz-emment related to autonwtive industrial polict;deGsion maker in Indonesin.